Mengkonstruk Multikulturalisme di Tengah Arus Global - Arif Muzayin Shofwan (PT PUSTAKA CENDEKIA GROUP, 2026)
The current era of globalization necessitates discourse in constructing multiculturalism. This qualitative descriptive paper, using a literature study, discusses how to construct multiculturalism amidst global currents. The data analysis uses content analysis, sorting data according to the research focus. This paper concludes that several elements must be constructed in the development of multiculturalism in education, including: theology, Islam, philosophy, conceptualization, traditional arts, human resource management, awareness, curriculum, social construction, and special needs. Meanwhile, several other elements that must be constructed in the development of multiculturalism are also carried out in three areas: (1) the element of terrorism, namely the handling of terrorism in Indonesian correctional institutions must always be considered, because terrorist prisoners are individuals who have been indoctrinated with religious dogma that is strongly misinterpreted; (2) the element of traditional theater, namely the reactualization of traditional theater as a medium for socializing multicultural values ​​is very effective. and (3) elements of conflict in the era of plurality, namely efforts to minimize conflict based on the main problems of life in the era of religious plurality, both between individuals and groups, which must be addressed.